METHODOLOGY OF REGIONAL ECONOMY OPTIMIZING - K. Ainabek (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2016)
Sustainable development of the national economy directly depends on the optimality of its composite parts. This can be addressed through the appropriate balance of the sectors and the regions, the inner parts of their structure based on a common criterion of the evaluation of cost variables characterizing the parameters of the functioning of the regional actors. This paper shows theoretical principles and economic-mathematical model of optimization of the regional economy and the relations between the center and the regions based on the author’s approach.